A copper ion sensor based on electrospinning flexible film and detection method
Through the flexible film preparation strategy based on electrospinning, the existing copper ion detection methods are solved, and the problems of high cost, long time and unsuitable for real-time monitoring are achieved, and high sensitivity and multiplexed copper ion detection is achieved, reducing detection costs and improving detection accuracy and efficiency.
Patent Information
- Application Number
- CN202211461103.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-11-16
AI Technical Summary
The existing copper ion detection methods have problems such as high cost, long time consuming, complex sample preparation and unsuitable for real-time monitoring. Traditional fluorescent probes have difficulties in storage, transportation and recycling, and heavy metal components are environmentally harmful.
Using a flexible film preparation strategy based on electrospinning, a fluorescent sensor with a high specific surface area and an open porous structure was prepared by preparing a metal organic frame and a dual-emitting fluorescent carbon dot powder in combination with electrospinning technology.
It realizes high sensitivity detection and multiplexing of copper ions, reduces detection costs, simplifies the sample preparation process, is suitable for real-time monitoring, and improves the accuracy and efficiency of detection.
Smart Images

Figure CN115746828B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescence analysis and detection, and relates to a copper ion sensor based on an electrostatic spinning flexible film. Background Art
[0002] Copper ions, as a common component of metalloenzymes, are essential trace elements for many biological systems. Since copper acts as a catalyst in various biological processes, copper is required by almost every organism. Its biochemical activities involve oxygen transport, hormone maturation, signal transduction, etc. Copper also plays an important role in biological, environmental and chemical systems. Copper is also an essential element for the formation of hemoglobin, red blood cells and bones in the human system. However, long-term exposure to high concentrations of copper ions can cause serious toxicity to the human body. Due to its huge usage, copper is also treated as a significant metal pollutant. Disorders in copper metabolism may also lead to serious neurodegenerative diseases such as Alzheimer's disease, Wilson's disease, amyotrophic lateral sclerosis and Menkes syndrome. Therefore, monitoring and regulating the concentration of copper ions is crucial for organisms. At present, some analytical methods and probes for selectively detecting copper ions have been developed, including potentiometric sensors, electrochemical sensors, atomic fluorescence spectroscopy, atomic absorption spectroscopy (AAS) and inductively coupled plasma mass spectrometry (ICP-MS), etc., which can detect copper with high sensitivity, but these methods have the disadvantages of high cost, long time consumption, complex sample preparation and unsuitability for real-time monitoring. Most of them require the use of complex instruments and cannot be applied to environmental media or for on-site analysis. Therefore, the practical application of this type of detection method is limited.
[0003] Fluorescent probes are considered to be the most effective tools for applications in biology, medicine, and chemistry due to their high sensitivity. In the past few decades, quantum dots have become one of the most widely used optical nanomaterials in various fluorescent sensors due to their high emission quantum yield and adjustable emission peak position. However, heavy metals are the basic elements that make up these quantum dot materials. Their potential toxicity and environmental hazards have hindered their further development. Compared with traditional semiconductor quantum dots and organic dyes, fluorescent carbon dots have advantages in many aspects, especially in simple and rapid synthesis, good water solubility, high biocompatibility, low toxicity and high photostability. Due to these outstanding properties, they can replace toxic quantum dots in many clinical and environmental applications.
[0004] Most fluorescent probes for ion detection require the use of aqueous solution systems, which greatly limits their practical applications. Fluorescent probes in aqueous solutions have certain difficulties in storage, transportation and recycling. In addition, disposable probes can cause serious environmental pollution. Therefore, compared with traditional fluorescent probes, flexible films have the advantages of being more stable, adjustable in shape and size, and easy to design, transport, operate and recycle. Fluorescent probes based on intensity changes are easily affected by factors such as probe concentration, excitation efficiency, poor selectivity, etc., resulting in amplified measurement errors. Compared with single-emission fluorescent probes, colorimetric fluorescent probes with multiple fluorescence centers or made of multiple fluorescent materials have more outstanding advantages. This type of probe is largely unaffected by the above-mentioned external factors, and also improves the accuracy of detection. Compared with traditional films based on fluorescence intensity changes, sensing films with two emission peaks can reduce the influence of external factors, such as excited state fluctuations, light masking, and local inhomogeneity of absolute intensity. Dual-emission sensing films that can be used for visual detection not only greatly improve the accuracy of data, but also effectively improve test efficiency. Therefore, the present invention proposes a flexible film preparation strategy based on electrospinning to achieve high sensitivity and multiplexed detection of copper ions. Summary of the invention
[0005] The purpose of the present invention is to provide a flexible film preparation strategy based on electrospinning to achieve high sensitivity and multiplexed detection of copper ions.
[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an electrospun flexible film, characterized in that: a metal organic framework is prepared; blue and yellow fluorescent carbon dots are prepared; then the two fluorescent carbon dots are simultaneously embedded in the metal organic framework; dual-emission fluorescent carbon dot powder is mixed with a polymer to prepare an electrospun flexible film; the metal organic framework is prepared by reacting indium nitrate hydrate and isophthalic acid dissolved in N,N-dimethylformamide in an oil bath.
[0007] The method for preparing the electrospinning flexible film comprises the following steps:
[0008] (1) dissolving indium nitrate hydrate and isophthalic acid in N,N-dimethylformamide and reacting them in an oil bath; after the reaction, centrifuging the solution sample and removing the supernatant, and drying it in an oven to obtain a white metal organic framework powder;
[0009] (2) dissolving blue fluorescent carbon dots and yellow fluorescent carbon dots in an ethanol solution, adding metal organic framework powder, magnetically stirring the mixed solution, centrifuging and removing the supernatant, and drying in an oven to obtain dual-emission fluorescent carbon dot powder;
[0010] (3) dissolving a thermoplastic polyurethane elastomer in N,N-dimethylformamide and performing magnetic stirring to obtain a thermoplastic polyurethane elastomer solution; adding a dual-emission fluorescent carbon dot powder to the thermoplastic polyurethane elastomer solution and performing magnetic stirring to obtain a fluorescent polymer solution;
[0011] (4) The fluorescent polymer solution was used for electrospinning to prepare flexible films.
[0012] In the step (1), the molar ratio of indium nitrate hydrate to isophthalic acid is 0.9-1.1:1.
[0013] In the step (1), the oil bath reaction conditions are 140-150° C. and 20-30 minutes.
[0014] In the step (4), the parameter conditions of the electrospinning system are: voltage 12-15 kV, needle-collector distance 12-15 cm, flow rate 0.9-1.1 mL / h.
[0015] The method for detecting copper ions using the copper ion sensor based on the electrospun flexible film comprises the following steps:
[0016] (1) preparing a series of copper ion standard solutions with different concentrations;
[0017] (2) completely immersing the electrospun flexible film according to claim 1 into the copper ion standard solution of step (1) to carry out a fluorescence quenching reaction; after the reaction is completed, taking out the film and drying it in an oven;
[0018] (3) measuring the fluorescence spectra of the films immersed in copper ion solutions of different concentrations, and establishing a standard fitting curve based on the linear relationship between the detected fluorescence intensity ratio and the copper ion concentration;
[0019] (4) immersing the film in an environmental water sample to be tested containing copper ions to perform a fluorescence quenching reaction; after the reaction is completed, taking out the film, drying it in an oven, and measuring the fluorescence spectrum intensity;
[0020] (5) Calculating the concentration of copper ions in the environmental water sample to be tested by standard fitting curve;
[0021] (6) placing the film after fluorescence quenching into a disodium ethylenediaminetetraacetic acid solution for fluorescence recovery reaction; after the reaction is completed, taking out the film and drying it in an oven; after drying, the fluorescence of the film is restored to the intensity before quenching so that it can be reused.
[0022] In the step (1), the concentration of the copper ion standard solution is 0.1-500 μM.
[0023] In the step (3), the linear detection range of the copper ion sensing standard curve is 0.5-100 μM.
[0024] Beneficial effects:
[0025] 1. The carbon dots of the present invention have simple raw materials and short reaction time, which is conducive to large-scale synthesis and application;
[0026] 2. The metal organic framework prepared by the present invention can realize the solid-state luminescence of carbon dots, expand the application scenarios of carbon dots, and improve the stability of carbon dots;
[0027] 3. The dual-emission fluorescent carbon dot powder prepared by the present invention is used as a ratiometric fluorescent probe, which can reduce the influence of external factors, greatly improve the accuracy of data, and effectively improve the test efficiency, and is suitable for visual detection;
[0028] 4. The electrospun flexible film prepared by the present invention has a unique ultra-high specific surface area and an open porous nonwoven structure, which can provide a unique sensing platform and exhibit extremely high fluorescence stability and sensitivity;
[0029] 5. Compared with the traditional aqueous solution type fluorescent probe, the electrospun flexible film prepared by the present invention is easy to design, transport, operate and recycle, and has a wide range of applications;
[0030] 6. The electrospun flexible film prepared by the present invention can be reused after being treated with a disodium ethylenediaminetetraacetic acid solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The fluorescence spectrum of the blue fluorescent carbon dots prepared in Example 1;
[0032] Figure 2 The fluorescence spectrum of the yellow fluorescent carbon dots prepared in Example 1;
[0033] Figure 3 This is a SEM image of the metal organic framework prepared in Example 2;
[0034] Figure 4 The fluorescence spectrum of the dual-emission fluorescent carbon dot powder prepared in Example 3;
[0035] Figure 5 The fluorescence spectra of the electrospun flexible film prepared in Example 5 after being treated with copper ion solutions of different concentrations;
[0036] Figure 6 This is a linear relationship diagram of the electrospun flexible film prepared in Example 5 after being treated with copper ion solutions of different concentrations;
[0037] Figure 7 This is a graph showing the CIE color coordinate changes of the fluorescence spectrum of the electrospun flexible film prepared in Example 5 after being treated with copper ion solutions of different concentrations. DETAILED DESCRIPTION
[0038] The present invention will be further explained below in conjunction with the embodiments and drawings. The following embodiments are only used to illustrate the present invention but are not intended to limit the scope of implementation of the present invention.
[0039] A method for preparing an electrospinning flexible film comprises the following steps:
[0040] (1) Dissolving citric acid and tris(hydroxymethyl)aminomethane in deionized water and reacting them in a microwave reactor; after the reaction, adding deionized water to dissolve, and removing insoluble solids by centrifugation; placing the solution sample in a dialysis bag for dialysis; and freeze-drying the dialyzed solution sample to obtain blue fluorescent carbon dots;
[0041] (2) dissolving phloroglucinol in formamide and reacting it in a microwave reactor; after the reaction, adding anhydrous ethanol to dissolve it, and removing the insoluble solid by centrifugation; placing the solution sample in a dialysis bag for dialysis; and freeze-drying the dialyzed solution sample to obtain yellow fluorescent carbon dots;
[0042] (3) dissolving indium nitrate hydrate and isophthalic acid in N,N-dimethylformamide and reacting them in an oil bath; after the reaction, centrifuging the solution sample and removing the supernatant, and drying it in an oven to obtain a white metal organic framework powder;
[0043] (4) dissolving blue fluorescent carbon dots and yellow fluorescent powder in an ethanol solution, adding metal organic framework powder, magnetically stirring the mixed solution, centrifuging and removing the supernatant, and drying in an oven to obtain dual-emission fluorescent carbon dot powder;
[0044] (5) dissolving a thermoplastic polyurethane elastomer in N,N-dimethylformamide and performing magnetic stirring to obtain a thermoplastic polyurethane elastomer solution; adding a dual-emission fluorescent carbon dot powder to the thermoplastic polyurethane elastomer solution and performing magnetic stirring to obtain a fluorescent polymer solution;
[0045] (6) The fluorescent polymer solution was used for electrospinning to prepare flexible films.
[0046] As a preferred embodiment of the present invention, in the step (1), the molar ratio of citric acid to tris(hydroxymethyl)aminomethane is 1:0.9.
[0047] As a preferred embodiment of the present invention, in step (1), the microwave reaction conditions are 800W and 4 minutes.
[0048] As a preferred embodiment of the present invention, in the step (2), the molar ratio of phloroglucinol to formamide is 1:27.
[0049] As a preferred embodiment of the present invention, in step (2), the microwave reaction conditions are 800W and 4 minutes.
[0050] As a preferred embodiment of the present invention, in the step (3), the molar ratio of indium nitrate hydrate to isophthalic acid is 1:1.
[0051] As a preferred embodiment of the present invention, in step (3), the oil bath reaction conditions are 140° C. and 30 minutes.
[0052] As a preferred embodiment of the present invention, in step (6), the parameter conditions of the electrospinning system are: voltage 15 kV, needle-collector distance 15 cm, flow rate 1 mL / h.
[0053] A method for detecting copper ions by using an electrospun flexible film comprises the following steps:
[0054] (1) preparing a series of copper ion standard solutions with different concentrations;
[0055] (2) completely immersing the prepared electrospun flexible film in the copper ion standard solution described in step (1) to carry out a fluorescence quenching reaction; after the reaction is completed, taking out the film and drying it in an oven;
[0056] (3) measuring the fluorescence spectra of the films immersed in copper ion solutions of different concentrations, and establishing a standard fitting curve based on the linear relationship between the detected fluorescence intensity ratio and the copper ion concentration;
[0057] (4) immersing the film in an environmental water sample to be tested containing copper ions to perform a fluorescence quenching reaction; after the reaction is completed, taking out the film, drying it in an oven, and measuring the fluorescence spectrum intensity;
[0058] (5) Calculating the concentration of copper ions in the environmental water sample to be tested by standard fitting curve;
[0059] (6) The film after fluorescence quenching is placed in a disodium ethylenediaminetetraacetic acid solution for fluorescence recovery reaction; after the reaction is completed, the film is taken out and dried in an oven; after drying, the fluorescence of the film is restored to the intensity before quenching and can be reused.
[0060] In the step (1), the concentration of the copper ion standard solution is 0.1-500 μM.
[0061] In the step (3), the linear detection range of the copper ion sensing standard curve is 0.5-100 μM.
[0062] Example 1
[0063] Method for preparing carbon dots:
[0064] (1) Weigh 0.4375 g of citric acid and 0.225 g of tris(hydroxymethyl)aminomethane) and dissolve them in 5 mL of deionized water, and react them in a microwave reactor. The reaction conditions are set to 800 W and 4 minutes. After the reaction, add 5 mL of deionized water to dissolve, and centrifuge to remove insoluble solids. Put the solution sample into a 1000 Da dialysis bag and dialyze it for 24 hours. After the dialysis, freeze-dry the solution sample to obtain blue fluorescent carbon dots.
[0065] (2) Weigh 0.5 g of phloroglucinol and dissolve it in 5 mL of formamide. The reaction is carried out in a microwave reactor with the reaction conditions set at 800 W and 4 minutes. After the reaction is completed, 5 mL of anhydrous ethanol is added to dissolve it and the insoluble solid is removed by centrifugation. The solution sample is placed in a 1000 Da dialysis bag and dialyzed for 24 hours. The dialyzed solution sample is freeze-dried to obtain yellow fluorescent carbon dots.
[0066] The emission spectra of the blue and yellow fluorescent carbon dots prepared in this example are as follows: Figure 1 , 2 As shown in the figure, it can be seen that the emission peak of the prepared blue fluorescent carbon dots is located at 412nm, and the emission peak of the prepared yellow fluorescent carbon dots is located at 532nm.
[0067] Example 2
[0068] Methods for preparing metal organic frameworks:
[0069] Weigh 0.015 g of isophthalic acid and 0.039 g of indium nitrate hydrate, dissolve them in 4 mL of N,N-dimethylformamide, and react in an oil bath at 140° C. for 30 minutes. After the reaction is completed, centrifuge and remove the supernatant. Dry the solid powder in an oven at 65° C. for 4 hours to obtain a white metal organic framework powder.
[0070] The morphology of the metal organic framework prepared in this example is as follows Figure 3 As shown in the figure, the prepared metal organic framework presents a spherical structure with a diameter of about 1 μm.
[0071] Example 3
[0072] Method for preparing dual-emission fluorescent carbon dot powder:
[0073] Take the blue fluorescent carbon dot powder of Example 1 to prepare a blue fluorescent carbon dot aqueous solution (0.1 mg / mL), and take the yellow fluorescent carbon dot powder of Example 1 to prepare a yellow fluorescent carbon dot aqueous solution (0.5 mg / mL); take 1 mL of the blue and yellow fluorescent carbon dot aqueous solutions respectively, add 20 mg of the metal organic framework powder, and stir vigorously for 15 minutes; after stirring, centrifuge and remove the supernatant; dry the solid powder in an oven at 65°C for 4 hours; and obtain a dual-emission fluorescent carbon dot powder.
[0074] The emission spectrum of the dual-emission fluorescent carbon dot powder prepared in this example is as follows: Figure 4 As shown in the figure, it can be seen that the fluorescence spectrum of the prepared dual-emission fluorescent carbon dot powder shows a double-peak emission, with peaks at 434nm and 562nm respectively.
[0075] Example 4
[0076] Method for preparing electrospun flexible films:
[0077] 0.8 g of thermoplastic polyurethane elastomer was weighed and dissolved in 4 mL of N,N-dimethylformamide, and magnetically stirred for 4 hours to obtain a thermoplastic polyurethane elastomer solution; 15 mg of the dual-emission fluorescent carbon dot powder in Example 3 was weighed and added to the thermoplastic polyurethane elastomer solution, and magnetically stirred for 2 hours to obtain a fluorescent polymer solution; the fluorescent polymer solution was used for electrospinning to prepare a flexible film, and the parameter conditions of the electrospinning system were set as: voltage 15 kV, needle-collector distance 15 cm, flow rate 1 mL / h.
[0078] Example 5
[0079] Method for establishing copper ion sensing standard curve:
[0080] A series of copper ion standard solutions with different concentrations were prepared, with a concentration range of 0.1-500 μM; the electrospun flexible film in Example 4 was completely immersed in the copper ion standard solutions with different concentrations to carry out a fluorescence quenching reaction; the film was taken out after the reaction for 15 minutes and dried in an oven at 50° C. for 30 minutes; the fluorescence spectra of the films after being immersed in copper ion solutions with different concentrations were measured respectively, and a standard fitting curve was established based on the linear relationship between the detected fluorescence intensity ratio and the copper ion concentration, and the linear range was calculated.
[0081] The fluorescence spectra of the electrospun flexible film obtained in this example after being treated with copper ion solutions of different concentrations are as follows: Figure 5 As shown in the figure, it can be seen that with the increase of copper ion concentration, the 562nm emission peak intensity gradually decreases, and the 434nm emission peak intensity remains unchanged.
[0082] The linear relationship diagram of the electrospun flexible film after being treated with copper ion solutions of different concentrations established in this embodiment is shown in FIG. Figure 6 As shown in the figure, it can be seen that within the copper ion concentration range of 0.5-100 μM, the film has an excellent linear response to copper ions, and the correlation coefficient can reach 0.997.
[0083] The CIE color coordinate change diagram of the fluorescence spectrum of the electrospun flexible film obtained in this embodiment after being treated with copper ion solutions of different concentrations is as follows: Figure 7As shown in the figure, it can be seen that with the increase of copper ion concentration, the chromaticity coordinates move from (0.305, 0.337) to (0.202, 0.145), and a great chromaticity change occurs, which is conducive to visual detection.
[0084] Example 6
[0085] Practical application methods of copper ion sensing:
[0086] The film is immersed in an environmental water sample to be tested containing copper ions to carry out a fluorescence quenching reaction; after reacting for 15 minutes, the film is taken out, dried in an oven, and the fluorescence spectrum intensity is measured; the concentration of copper ions in the environmental water sample to be tested is calculated by a standard fitting curve; the film after fluorescence quenching is placed in a disodium ethylenediaminetetraacetic acid solution for a fluorescence recovery reaction; after the reaction is completed, the film is taken out and dried in an oven; the fluorescence of the dried film recovers to the intensity before quenching and can be reused.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrospun flexible film, characterized in that: Prepare a metal organic framework; prepare blue and yellow fluorescent carbon dots; then embed the two fluorescent carbon dots into the metal organic framework at the same time to obtain a dual-emission fluorescent carbon dot powder; add the dual-emission fluorescent carbon dot powder into a thermoplastic polyurethane elastomer solution, perform magnetic stirring, and obtain a fluorescent polymer solution for preparing an electrospinning flexible film; the metal organic framework is prepared by reacting indium nitrate hydrate and isophthalic acid dissolved in N,N-dimethylformamide in an oil bath; The method for preparing blue fluorescent carbon dots is as follows: citric acid and tris(hydroxymethylaminomethane) are dissolved in deionized water and reacted in a microwave reactor; after the reaction, water is added to dissolve, and insoluble solids are removed by centrifugation; dialyzation is performed, and the dialyzed solution sample is freeze-dried to obtain blue fluorescent carbon dots; The method for preparing yellow fluorescent carbon dots is as follows: phloroglucinol is dissolved in formamide, and reacted in a microwave reactor. After the reaction is completed, anhydrous ethanol is added to dissolve it, and the insoluble solid is removed by centrifugation. The dialyzed solution sample is freeze-dried to obtain yellow fluorescent carbon dots.
2. The method for preparing the electrospun flexible film according to claim 1, characterized in that: The steps are: (1) Dissolving indium nitrate hydrate and isophthalic acid in N,N-dimethylformamide and reacting them in an oil bath; after the reaction, centrifuging the solution sample and removing the supernatant, and drying it in an oven to obtain a white metal organic framework powder; (2) dissolving blue fluorescent carbon dots and yellow fluorescent carbon dots in an ethanol solution, adding metal organic framework powder, subjecting the mixed solution to magnetic stirring, centrifuging and removing the supernatant, and drying in an oven to obtain dual-emission fluorescent carbon dot powder; (3) dissolving a thermoplastic polyurethane elastomer in N,N-dimethylformamide and performing magnetic stirring to obtain a thermoplastic polyurethane elastomer solution; adding a dual-emission fluorescent carbon dot powder to the thermoplastic polyurethane elastomer solution and performing magnetic stirring to obtain a fluorescent polymer solution; (4) The fluorescent polymer solution was used for electrospinning to prepare flexible films.
3. The method for preparing an electrospun flexible film according to claim 2, characterized in that: In the step (1), the molar ratio of indium nitrate hydrate to isophthalic acid is 0.9-1.1:
1.
4. The method for preparing an electrospun flexible film according to claim 2, characterized in that: In the step (1), the oil bath reaction conditions are 140-150° C. and 20-30 minutes.
5. The method for preparing an electrospun flexible film according to claim 2, characterized in that: In the step (4), the parameter conditions of the electrospinning system are: voltage 12-15 kV, needle-collector distance 12-15 cm, flow rate 0.9-1.1 mL / h.
6. A method for detecting copper ions using a copper ion sensor based on the electrospun flexible film of claim 1, characterized in that: The following steps are involved: (1) Prepare a series of copper ion standard solutions with different concentrations; (2) completely immersing the electrospun flexible film of claim 1 into the copper ion standard solution of step (1) to carry out a fluorescence quenching reaction; after the reaction is completed, taking out the film and drying it in an oven; (3) Measure the fluorescence spectra of the films after being immersed in copper ion solutions of different concentrations, and establish a standard fitting curve based on the linear relationship between the detected fluorescence intensity ratio and the copper ion concentration; (4) Immersing the film in an environmental water sample containing copper ions to be tested to perform a fluorescence quenching reaction; after the reaction is completed, taking out the film, drying it in an oven, and measuring the fluorescence spectrum intensity; (5) Calculate the concentration of copper ions in the environmental water sample to be tested through the standard fitting curve; (6) The film after fluorescence quenching is placed in a disodium ethylenediaminetetraacetic acid solution for fluorescence recovery reaction; after the reaction is completed, the film is taken out and dried in an oven; after drying, the fluorescence of the film is restored to the intensity before quenching so that it can be reused.
7. The method according to claim 6, characterized in that: In the step (1), the concentration of the copper ion standard solution is 0.1-500 μM.
8. The method according to claim 6, characterized in that: In the step (3), the linear detection range of the copper ion sensing standard curve is 0.5-100 μM.